RESEARCHING PROSPECTS FOR THE DEVELOPMENT OF THE FLOW OF TRANSIT CARGO THROUGH THE KAMCHIK PASS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This scientific article highlights the specific features of the Kamchik Pass, especially the complexity of the road, and therefore the benefits that will come from increasing the flow of transit cargo. Also, the article shows the solution of the problems that may arise in this direction through the "Transportation" laws of our republic.